Extraction of kinetic energy in the part of Aceh Waters. Issue 1 (May 2021) - Siregar, A M; Ikhwan, M; Haditiar, Y; Wafdan, R; Muhammad, M; Ramli, M; Muchlisin, Z A; Rizal, S
Abstract: This research is a preliminary study regarding the extraction of kinetic energy from sea tides in Aceh's waters. Aceh's waters have a reasonably long coastline (> 2000 km), which has not been studied and utilized much. The extraction of kinetic energy from ocean tides is based on the speed of currents and turbines. Hydrodynamic verification is based on sea-level data from TPXO7.2 and Geospatial Indonesia Agency (GIA). The tidal data is sufficiently consistent with the verification data from TPXO7.2 and GIA. Based on the results, the model succeeded in accurately describing the hydrodynamics currents in the research domain based on comparative verification data. The velocity of M2 tidal flow in the waters of West Aceh is relatively low, particularly in the waters of Ulee Lheue is 0.018 m/s while in Calang waters, it is 0.025 m/s. The maximum tidal energy in Ulee Lheue waters is 9, 142 × 10 −2 kW, with a daily power of 4.63 × 10 3 kW. In Calang waters, the maximum energy is 2, 449 × 10 −1 kW, while the daily power is 1, 0167 × 10 4 kW. These results indicate that Calang Waters (Aceh Jaya district) had more significant potential for tidal currents and energy than Ulee Lheue Waters (Aceh Besar district).